1991
DOI: 10.1084/jem.174.1.253
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ICAM-2 and evidence for a third counter-receptor for LFA-1.

Abstract: In an endeavor to further characterize human intercellular adhesion molecule-2 (ICAM-2), two murine monoclonal antibodies (mAb) were generated to ICAM-2 transfected COS cells, and designated CBR-IC2/1 and CBR-IC2/2. Immunoprecipitated, reduced ICAM-2 migrated as a broad band of Mr 60,000 in sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Treatment with N-glycanase revealed a peptide backbone of Mr 31,000, consistent with the size predicted from the cDNA. ICAM-2 had a broad distribution on hematopoie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
207
1
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 448 publications
(219 citation statements)
references
References 53 publications
9
207
1
2
Order By: Relevance
“…Rat ECFCs express endothelial surface markers VCAM-1 and ICAM-2 15,24 . They also express CD34 and c-Kit, cell-surface antigens previously identified on endothelial and hematopoietic progenitor cells 15,25 (Figure 7).…”
Section: Rat Lung Ecfcs Isolated By This Protocol Also Demonstrate Almentioning
confidence: 99%
“…Rat ECFCs express endothelial surface markers VCAM-1 and ICAM-2 15,24 . They also express CD34 and c-Kit, cell-surface antigens previously identified on endothelial and hematopoietic progenitor cells 15,25 (Figure 7).…”
Section: Rat Lung Ecfcs Isolated By This Protocol Also Demonstrate Almentioning
confidence: 99%
“…These proteins were shown to serve as ICAM-2 ligands on other leukocytes [13,15,16]. We therefore expected these molecules to account for the ICAM-2-dependent TEM of immature DC.…”
Section: Discussionmentioning
confidence: 99%
“…Geijtenbeek et al [12] have shown that this interaction enables rolling of DC-SIGN-transfected cells on ICAM-2 and transmigration of DC across endothelial monolayers. For homeostatic extravasation of DC, the DC-SIGN-ICAM-2 interaction is of particular interest since ICAM-2 is constitutively expressed on endothelium and does not require inflammatory stimuli for high-density expression as do other endothelial adhesion molecules like ICAM-1 and the endothelial selectins [13,14]. In this respect it is especially interesting that Geijtenbeek et al [12] found that the DC-SIGN-ICAM-2 interaction does mediate migration of immature DC not only across activated but also across resting endothelium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICAM-2 (CD102) is constitutively expressed on vascular endothelial cells (45) and is a ligand for leukocyte ␤ 2 -integrins CD11a/CD18 and CD11b/CD18 (145,249,291). In vitro, ICAM-2 appears to play a role in neutrophil (116) and eosinophil (83) transendothelial migration.…”
Section: Neutrophil Migration Across Vascular Endotheliummentioning
confidence: 99%